Historical trends in the size of US Olympic female artistic gymnasts - Sands, W. A.; Slater, C.; McNeal, J. R.; Murray, S. R.; Stone, M. H. (International Journal of Sports Physiology and Performance, 2012)
The lay press, scientists, and physicians appear to believe that gymnasts are continually getting smaller and that their "smallness" is a health risk. Purpose: To assess the historical changes in the size and age of the US women`s Olympic gymnastics teams from 1956 to 2008. Methods: The official records from the US Olympic Committee and USA Gymnastics of Olympic team members were assessed at 2 levels: individual height, mass, age, and body-mass index (BMI) and the team performance scores and rankings. Fourteen Olympic teams with a total of 106 team members, including the alternates, were included. Trend analyses were conducted using linear and polynomial models. Results: Simple linear correlations indicated that since 1956, height, mass, age, BMI, and team Olympic rank have been declining. However, second-order polynomial curve fits indicated that in the last 4 Olympic Games the members of the US women`s gymnastics teams have been getting larger. Conclusion: Women Olympic gymnasts were getting smaller through approximately the 1980s and early 1990s. Since then the size of these gymnasts has increased. The minimum-age rule modifications may have played a role in athlete size changes along with a shift from the near dominance of the former communist Eastern Bloc.